Assessment of Training Programmes in the South African Police Service in Northern Cape Province - (:unkn) unknown (My University, 2023)
The purpose of this article is to assess the outcomes of T&D programs provided by the Division of Training and Development. To validate the research question and authenticate the problem statement, this article used qualitative research methodology. moreover, this article intended to establish whether there is a significant effect or impact on the performance of trainees and in their workplace that can be linked to the training conducted by the Division Training and Development. The research focused largely on post-training M&E mechanisms to determine the outcome of training conducted, and in the study the term “impact assessment” was predominantly used as most participants were familiar with the term as compared to “outcomes assessment”. Qualitative research includes field notes, conversations, recorded interviews, photographs and memos, amongst others. Based on the research findings, this article makes actionable recommendations. Training is a strategic mechanism for achieving and delivering efficient and competent public security. It is also used to assess organizational performance, as fully trained and skilled employees will be capable of returning to the workplace and providing optimal service in a safe and well-organized manner.
Keywords: African Research